Kesiapan Guru Sekolah Dasar dalam Menerapkan Kurikulum Merdeka Belajar di Kecamatan Peukan Bada Kabupaten Aceh Besar - Isfaniari, Isfaniari; Mardhatillah, Mardhatillah; Sariakin, Sariakin; Sari, Siti Mayang (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to describe the readiness of elementary school teachers in implementing the Independent Learning Curriculum in Peukan Bada District, Aceh Besar Regency. The research was carried out at Peukan Bada State Elementary School I and Lamteh State Elementary School. This research uses field research with descriptive research and a qualitative approach. Data collection techniques can be done by observation, interviews, questionnaires, documentation. Data analysis in the field includes recording, coding and temporary interpretation of various information obtained at various research steps. The results of the research prove that there is teacher readiness in implementing the independent learning curriculum, the need for the use of the Independent Learning Platform by teachers who will implement the independent learning curriculum so that it can support the student-friendly learning process as expected in the independent learning curriculum